PENGARUH METODE INSERSI PADA PEMBELAJARAN ILMU PENGETAHUAN ALAM (IPA) TERHADAP KARAKTER RELIGIUS SISWA KELAS 5 SD AL AZHAR SYIFA BUDI CIBINONG - Yatini Yatini; Retno Triwoelandari (Yayasan Akrab Pekanbaru, 2018)
This study aims to determine the differences of religious character possessed by students in the class that has applied the Insersi method with a class that does not apply the Insertion method on science learning in grade V at SD Al-Azhar Syifa Budi Cibinong Bogor. The sample in this study are two classes; control class and experiment class of 48 students each. The method used in this study is a quasi-experimental method. Data collection using pretest and posttest. The data were analyzed by t test with Paired Samples Test and Independent Samples Test. Keyword: Method, insertion, character, student